Pengaruh Alat Bantu Terhadap Kemampuan Tendangan T Atlet Pencak Silat Kota Palopo - Andi Alfa Reza; Hidayat, Rachmat; Pajarianto, Hadi; Riswanto, A Heri (Jurnal Porkes, 2025)
This study aims to determine the effect of using tools on improving T kicking ability in pencak silat athletes in Palopo City. This study uses a quantitative approach with a pretest and posttest experimental design. This study uses a quantitative approach with a causal and experimental study design. Ten athletes were selected through purposive sampling, based on specific criteria relevant to the research objectives. The research instrument was an observation sheet designed to assess T-kick ability through five main indicators: speed, accuracy, strength, balance, and movement coordination. Data were obtained through skill tests, direct observation, and documentation. Furthermore, the data were analyzed using descriptive statistical tests, normality tests, homogeneity tests, and paired sample t-tests using the SPSS program. The results showed a significant increase in T-kick ability after using the tool, with a pretest average score of 65.30 increasing to 79.60 on the posttest. The t-test results produced a significance value of 0.001 (p < 0.05), which indicates that the use of tools has a significant effect on improving the T-kick ability of pencak silat athletes. It can be concluded that the use of tools in training has a significant effect on improving the T-kick ability of pencak silat athletes in Palopo City.